Análisis espacial y del entorno físico de accidentes de tránsito en la ciudad de Resistencia, Chaco, Argentina - Martín Chaparro; Akram Hernández-Vásquez; Alejandro Parras (Salud Colectiva, 2018)
Traffic accidents are an emerging problem in cities with high mobility and little urban planning. Evidence is lacking in Argentina regarding the relationship between the environment and accident occurrence; we therefore conducted a geospatial analysis and estimated the risk of accidents and their possible association with the characteristics of the physical environment in the city of Resistencia, Argentina occurring in 2012. Kernel density estimates were used for the spatial distribution of accidents and in parallel an observational, analytical study was carried out to analyze the factors associated with accident occurrence. The results show three critical areas (in the northwest, center and south of the city) with greater accident frequency. Environmental factors that were associated with the occurrence of accidents were the presence of street lighting (23% greater), the presence of a tree close to the road (47% greater), the presence of a traffic light (28% greater), and if the road was a major avenue (122% greater) and had curves (129% greater). This study shows the city of Resistencia to be in a situation of urban vulnerability due not only to its socioeconomic status but also to the unequal development compared to neighboring cities, a reality that fosters an unfavorable environment.